Assessing Flare Combustion Efficiency using Imaging Fourier Transform Spectroscopy. (October 2021) - Miguel, RB; Talebi-Moghaddam, S; Zamani, M; Turcotte, C; Daun, KJ
Highlights: Can imaging transform Fourier spectrometers quantify flare combustion efficiency?. Species column densities found from spectroscopic model. Velocities found from optical flow algorithm. Inferring column densities and velocity fields are both mathematically ill-posed. Technique works but is susceptible to scene change artifacts. Abstract: Flaring plays a critical role in reducing the environmental impact of upstream oil and gas processing by converting methane and other gaseous hydrocarbons into CO2, which has a lower global warming potential. This process is highly efficient under ideal conditions but efficiency may be significantly lower under certain scenarios such as fuel stripping under crosswind and emission of volatile organic compounds and unburned fuels due to over-aeration or over-steaming in assisted flares. This study assesses the potential of using imaging Fourier transform spectrometers (IFTSs) to directly measure combustion efficiency by combining species column densities estimated from a spectroscopic model with intensity-weighted velocities found using an optical flow model. Simulated measurements using a computational fluid dynamics (CFD)-large eddy simulation of a flare in a crosswind are used to establish the technique's viability, followed by experimental measurements on a heated gas vent to validate the optical flow model. Finally, preliminary measurements are carried out on a laboratory-scale steam- and air-assisted flare. While the simulated measurements and heated vent experiments support the feasibility of this approach, experimentally-derived spectra from the lab-scale flare were contaminated with artifacts attributed to turbulent fluctuations, which complicates the quantitative interpretation of the IFTS data.